2018
DOI: 10.1016/j.radonc.2018.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Tracking tumor biology with radiomics: A systematic review utilizing a radiomics quality score

Abstract: In this study, we performed a systematic literature search linking radiomics to tumor biology. All but two studies (n = 39) revealed that radiomic features derived from ultrasound, CT, PET and/or MR are significantly associated with one or several specific tumor biologic substrates, from somatic mutation status to tumor histopathologic grading and metabolism. Considerable inter-observer differences were found with regard to RQS scoring, while important questions were raised concerning the interpretability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(165 citation statements)
references
References 57 publications
5
157
0
3
Order By: Relevance
“…Moreover, a previous study reported that IA tends to appear more heterogeneous on CT images than PM [30]. Therefore, we hypothesize that radiomics features describing density and heterogeneity are related to tumor biology and pathology and are an excellent predictor for identification of IA [25]. CT and positron emission tomography radiomics studies have shown predictive features could be a surrogate of lesion volume and knowledge of which features correlate highly with volume is therefore important [31][32][33].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, a previous study reported that IA tends to appear more heterogeneous on CT images than PM [30]. Therefore, we hypothesize that radiomics features describing density and heterogeneity are related to tumor biology and pathology and are an excellent predictor for identification of IA [25]. CT and positron emission tomography radiomics studies have shown predictive features could be a surrogate of lesion volume and knowledge of which features correlate highly with volume is therefore important [31][32][33].…”
Section: Discussionmentioning
confidence: 92%
“…This study was followed by the Transparent Reporting of a Multivariable Prediction Model for Individual Prognosis or Diagnosis (TRIPOD) guidelines [24]. The radiomics quality score (RQS) was used to evaluate the radiomics workflow [25]. Pearson's chi-squared test was used for the statistical analysis of essential demographic characteristics.…”
Section: Tripod Guidelines Radiomics Quality Score and Statistical mentioning
confidence: 99%
“…In principle, connected biomarkers open new avenues to therapeutic paths, and allows assessment of emerging digital biomarkers (12). Here, we demonstrate the applicability of a PM network approach in onco-radiomics (13,14). We considered patients affected by intracranial ependymoma whose response to radiotherapy was assessed by MRI.…”
Section: Our Contributionmentioning
confidence: 99%
“…Nevertheless, one of the main reasons for the still limited impact of radiomics on everyday practice may be the difficulty in interpreting the relevant imaging biomarkers (such as the radiomic features) in biological terms. 30 Future studies will need to investigate how tumour biology and phenotypes translate into imaging features. Furthermore, most of the results need to be validated on large prospective independent cohorts.…”
Section: Radiomics For Cancer Diagnosismentioning
confidence: 99%